THE ROLE OF HADITH IN DEVELOPING STUDENT CHARACTER - Alfi Lutfiyah; Abu Bakar, Romlah; Abdul Ghofur (AZKIA : Jurnal Aktualisasi Pendidikan Islam, 2025)
Hadith as one of the main sources of Islamic teachings has a very important role in developing students' character. In Islam, reason is seen as a gift that must be educated to be able to think critically, rationally, and based on religious values, while character includes the formation of noble morals that are the basis of human behavior. This study aims to analyze the role of hadith in developing students' character and its relevance in today's life. The research method used is qualitative with a descriptive-analytical approach through literature study, which involves an in-depth study of hadiths related to Education and character formation. The results of the study show that the hadith of the Prophet SAW provides comprehensive direction in character development through recommendations to seek knowledge and think critically, as well as building character through internalization of moral values ​​such as honesty, patience, and compassion. The synergy between Education and character not only forms intelligent and moral individuals, but also supports the creation of harmonious and civilized students. This study emphasizes the importance of integrating hadith teachings into the education system to create students with noble characters in accordance with the goals of Islamic Religious Education.